Fatal patients with severe fever with thrombocytopenia syndrome in China. (December 2022) - Zhao, Jing; Ge, Hong-Han; Wang, Gang; Lin, Lei; Yuan, Yang; Xu, Yan-Li; Liu, Yuan-Ni; Lu, Qing-Bin; Zhang, Xiao-Ai; Cui, Ning; Yuan, Chun; Li, Jian-Xiong; et al.
Highlights: A total of 11 laboratory indicators persistently deviated from normality of fatal severe fever with thrombocytopenia syndrome cases. The critical time points of fatal severe fever with thrombocytopenia syndrome cases were 6-9 days after disease onset. Laboratory indicators differed across age and sex groups. Fatal cases with a shorter clinical course had more severe liver and kidney damage. Abstract: Objectives: Severe fever with thrombocytopenia syndrome (SFTS) is an emerging tick-borne infectious disease with a high case fatality rate. Key gaps remained as to the assessment of the clinical picture in fatal cases. Methods: A retrospective study was performed on 496 patients with fatal SFTS. The dynamic pattern of clinical manifestations and laboratory indicators were delineated. Results: The mean age of the fatal cases was 69.0 years (standard deviation: 9.3), and 52.8% were male. The median clinical course from disease onset to death was 11 (interquartile range: 10-13) days. A total of 11 laboratory indicators (neutrophil %, platelet, aspartate aminotransferase, aspartate aminotransferase/alanine transaminase, lactate dehydrogenase, creatine kinase, cystatin C, D-dimer, activated partial thromboplastin time, thrombin time, glucose) persistently deviated from normality across hospitalization. The critical time points when the rapid worsening of the indicators was at 6-9 days after disease onset. Alanine transaminase, AST, lactate dehydrogenase, total bile acid, gamma-glutamyl transpeptidase, and glucose were all elevated to a more pronounced level in fatal cases of those aged ≤70 years. Conclusion: The fatal outcome was developed in rather a short course after the disease onset of SFTS. High vigilance should be put on the key time points when the severe worsening and severe complications occur.